2015
DOI: 10.1038/srep07694
|View full text |Cite
|
Sign up to set email alerts
|

Wide Field-of-View Fluorescence Imaging of Coral Reefs

Abstract: Coral reefs globally are declining rapidly because of both local and global stressors. Improved monitoring tools are urgently needed to understand the changes that are occurring at appropriate temporal and spatial scales. Coral fluorescence imaging tools have the potential to improve both ecological and physiological assessments. Although fluorescence imaging is regularly used for laboratory studies of corals, it has not yet been used for large-scale in situ assessments. Current obstacles to effective underwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…The first involves recent development in the field of automated image analysis using deep Convolutional Neural Networks (CNNs) which have dramatically increased the classification accuracy for a wide range of images [89,90]. The second involves the opportunity to complement the RGB camera used here with multi-spectral or fluorescence cameras [91]. In this case, collecting additional spectral information could improve the ability to detect additional spectral signals, thereby improving precision and accuracy when distinguishing visually overlapping categories.…”
Section: Future Directionsmentioning
confidence: 99%
“…The first involves recent development in the field of automated image analysis using deep Convolutional Neural Networks (CNNs) which have dramatically increased the classification accuracy for a wide range of images [89,90]. The second involves the opportunity to complement the RGB camera used here with multi-spectral or fluorescence cameras [91]. In this case, collecting additional spectral information could improve the ability to detect additional spectral signals, thereby improving precision and accuracy when distinguishing visually overlapping categories.…”
Section: Future Directionsmentioning
confidence: 99%
“…Even though the camera was placed on a frame positioned on the seabed, there were still small movements that caused slight differences between the images. In Treibitz et al (2015) the images were aligned manually. In the present case, to overcome these movements and register the image pairs automatically, we developed an image registration algorithm written in MATLAB (Mathworks, Inc.; Akkaynak, 2017).…”
Section: Image Subtraction For Daytime Fluorescencementioning
confidence: 99%
“…Consequently, most studies detecting fluorescence in situ take place at night to avoid ambient light illumination (Piniak et al, 2005;Baird et al, 2006). Treibitz et al (2015) showed that fluorescence could be imaged during daytime by subtracting the ambient light image (captured with the strobes off).…”
Section: Introductionmentioning
confidence: 99%
“…In satellite remote sensing, coral observation is disturbed by waves on the sea surface and the absorption and scattering of light in seawater [5]. Underwater investigations are hindered by the narrow field of view (hereafter FOV) and slow survey speed [6]. The present study attempts to improve coral observation with a boat-based observation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Because these damages diminish the coral cover within a short time, reliable and frequent coral viability checking is essential for coral monitoring. To assess coral viability, we can exploit the fluorescence properties of corals [6]. The surface tissue of most corals contains innate fluorescent proteins, which emit at blue-to-green wavelengths (400-570 nm) under ultraviolet (hereafter UV) excitation [8].…”
Section: Introductionmentioning
confidence: 99%